The mestizo mind : the intellectual dynamics of colonization and globalization - Gruzinski, Serge (Routledge, 2002)
Mestizo: a person of mixed blood; specifically, a person of mixed European and American Indian ancestry. Serge Gruzinski, the renowned historian of Latin America, offers a brilliant, original critique of colonization and globalization in The Mestizo Mind. Looking at the fifteenth-century colonization of Latin America, Gruzinski documents the mélange that resulted: colonized mating with colonizers; Indians joining the Catholic Church and colonial government; and Amerindian visualizations of Jesus and Perseus. These physical and cultural encounters crea.